Changes in internship programmes and graduate employment in the context of the COVID-19 - Yin, Hao-yue (2022)
The sudden outbreak of the epidemic at the end of 2019 has once again put graduate employment in jeopardy. To effectively mitigate the trend of declining employment rates for recent graduates, and based on researchers' studies of internship programmes, this thesis proposes the idea that the implementation of internship programmes in the context of the epidemic might be a measure to alleviate the employment difficulties of graduates. The subject of this thesis is a large internet company in Shandong Province, China, where the author worked as an intern during the outbreak in late 2019. To be able to explore this area in more depth, this thesis took the form of semi-structured interviews with ten internship program stakeholders (two HRs in charge of the internship program, two project managers leading interns and six interns) in the surveyed company who had experience with the epidemic. The data was collated to show that the main impact of the epidemic on internship programmes was a change in the form of work and that the adoption of online internships or the resumption of normal offline internship programmes in the context of the epidemic had a positive impact on graduate employment. This applies to internet companies with the ability to work online. This study fills a gap in the field of post-epidemic employment for Chinese graduates, and the findings can also be used in practice to improve the position of internship programmes in companies. In future research, consideration could be given to expanding the geographical scope of research into the employment impact of internship programmes.